(untitled) (Medical Forum Monthly, 2020)
Objective: To find frequency of asthma chronic obstructive pulmonary disease overlap syndrome in patients with chronic obstructive pulmonary disease. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Department of Medicine, Avicenna Medical & Dental College, Lahore from November 2019 to April 2020. Materials and Methods: Two hundred patients of both genders presented with chronic obstructive pulmonary disease were taken. The name, age, and gender, contact details and BMI were recorded. Five ml of venous blood was drawn for IgG and CBC and bronchodilator response was assessed on spirometry. All clinical diagnosis and procedures were made by senior consultant. Results: The mean age of all cases was 51.63±7.17 years with minimum and maximum age as 40 and 64 years. There were 115(57.5%) male and 85(42.5%) female cases. The mean weight, height and body mass index were 93.19±18.05, 1.83±0.18 and 27.90±4.10 respectively. A total of 70 (35%) cases were obese and 130 (65%) cases were non-obese in this study. According to operational definition the frequency of ACOS was noted in 39(19.5%) and 161(80.5%) cases did not have ACOS. When data was stratified, the frequency of ACOS was statistically same in both age groups, gender, obese and non-obese and regardless of duration of COPD, p-value > 0.05. Conclusion: The frequency of ACOS was diagnosed 19.5% of cases that is higher percentage. So cases with COPD must be diagnosed ACOS and should be managed by prescribing more appropriate medication such as inhaled corticosteroids early in the course of the disease. Through early intervention we can reduce the related complications and mortality.